ALGORITHMIC METHOD IN DYNAMIC DOSING SYSTEMS BASED ON WEIGHT MEASURING PRINCIPLES (ETIMA, 2024)
Algorithmic method and a technical solution are suggested in order to increase performance of worm-and-wheel dosing systems (bagging machines) operating on weight measuring principles. The results from the weight measuring processed by using Fourier transformation and extrapolation of the weight transformation curve. The method applied in an algorithm for controlling weight in two situation of the working cycle of the flour-bagging machine: selective weight measurement of net and tare. The algorithm allows increasing the productivity without changing the mechanical design of the machine. This improvement helps make the machine competitive with the best Western packaging machine manufacturers.
Keywords: Bulk dosing systems; dynamic weigh; extrapolation; algorithmic method